Ketangguhan Akademis dan Kesejahteraan Psikologis pada Mahasiswa - Rayda Zhavira; Listyati Setyo Palupi (Airlangga University Press, Universitas Airlangga, 2022)
Psychological well-being has an important role in achieving academic success. However, the psychological well-being of college students tends to decrease as the years of study increase. This study aims to determine whether there is a correlation between academic hardiness and student psychological well-being. Quantitative research with a cross-sectional design was conducted on 148 students at Airlangga University. The Revised Academic Hardiness Scale and Javanese Psychological Well-Being Scale were used as data collection tools. The results of the hypothesis test show that there is a positive correlation with moderate strength between academic hardiness and psychological well-being in college students. The results of this study are useful for the development of positive psychology studies in the context of college students.